CSIG-10. GENOTYPE – KINOME GUIDED DEVELOPMENT OF PRECISION EGFR-TARGETED THERAPEUTICS FOR GLIOBLASTOMA. (9th November 2020) - Smithberger, Erin; Shelton, Abigail; Butler, Madison; Stamper, Allie; Bash, Ryan; Angus, Steven; East, Michael; Johnson, Gary; Berens, Michael; Furnari, Frank; Miller, C Ryan
Abstract: Glioblastoma (GBM) is an aggressive primary brain tumor with poor survival and limited treatment options. However, it is an attractive candidate for precision therapeutic approaches due to the frequency of amplification and/or activating mutations in the epidermal growth factor receptor (EGFR) gene and the availability of several brain penetrant second- and third-generation EGFR tyrosine kinase inhibitors (TKI). We used comprehensive molecular profiling of a panel of genetically engineered mouse astrocyte models to examine whether mutational profiles, particularly EGFR and PTEN status, could be used to identify kinases upregulated in specific mutational backgrounds. Using RNA-seq and multiplex inhibitor bead/mass spectrometry (MIB-MS) to analyze the kinase transcriptomes and proteomes, respectively, we have identified several potential targets for combination therapy. Overexpression of wild type EGFR in immortalized, Cdkn2a -/ - astrocytes resulted in mild rewiring of the GBM kinome. Only 5 kinases aside from EGFR itself were overexpressed on either the transcript or protein levels. One overexpressed kinase, Hck, has been shown to be involved in cell survival, proliferation, adhesion, and migration. In contrast, overexpression of EGFRvIII, a constitutively active, extracellular domain truncation mutant of EGFR, resulted in significant alteration of the GBM kinome – 81 kinases showed differential expression, with 27 upregulated. One potentially attractive target among these was Cdk6, a drug-targetable, prognostically significant cyclin-dependent kinase implicated in proliferation, migration, and invasion. Finally, overexpression of EGFRvIII in cells lacking Pten dysregulated 46 kinases, including 15 upregulated. One particularly interesting target in these cells was Ddr2, a tyrosine kinase involved in migration, invasion, and extracellular matrix remodeling. We conclude that Hck, Cdk6, and Ddr2 represent attractive targets for therapeutic intervention in their relevant genetic contexts. These findings also suggest that molecular diagnostics for EGFR and PTEN status may be useful in guiding development of rational, EGFR TKI-centric drug combinations.